2014
DOI: 10.1007/s00213-014-3497-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a proposed “three-criteria” cocaine addiction model for use in reinstatement studies with rats

Abstract: Our data highlight the independence of behavioral aspects of a rat addiction-like phenotype and suggest that some of these behavioral criteria may be altogether absent in some rat populations. Furthermore, our results suggest a closer review and analysis of some parameters used in this protocol and its global utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Persistence of alcohol seeking was evaluated daily throughout the training period. We ran a cluster analysis to identify a subgroup of rats that increased their response during the drug free period over time, as other laboratories have failed to capture this behavioral criterion (Waters et al, 2014). By clustering rats based on their persistence in lever pressing in the absence of alcohol availability, we were able to determine a subpopulation of rats (38% of msP and 26% of Wistars) that were highly persistent in lever pressing.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of alcohol seeking was evaluated daily throughout the training period. We ran a cluster analysis to identify a subgroup of rats that increased their response during the drug free period over time, as other laboratories have failed to capture this behavioral criterion (Waters et al, 2014). By clustering rats based on their persistence in lever pressing in the absence of alcohol availability, we were able to determine a subpopulation of rats (38% of msP and 26% of Wistars) that were highly persistent in lever pressing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, arguing against general learning deficits, abnormal punished reward-seeking in these mice were not accompanied by deficits in initial operant learning or in persistent reward-seeking during reward absence or progressive ratio responding for reward ( Deroche-Gamonet et al 2004; Radwanska and Kaczmarek 2012). In this context, recent studies in rats have found that chronic exposure to ethanol or cocaine causes changes in two or all three of these measures (Belin et al 2011; Deroche-Gamonet et al 2004; Jonkman et al 2012; Vendruscolo et al 2012) (but see Waters et al 2014). The behaviorally selective (punishment-specific) phenotypic profile shown by the GluN2B CxNULL mice demonstrates that while the mechanisms regulating these various measures are likely to be overlapping, they can also be dissociated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some laboratories have failed to implement this model [98] that is technically challenging, as it requires the maintenance of patent catheters for more than 70 days on large cohorts (at least 40 rats, the smallest cohort out of which enough addicted rats can be reliably identified). Additionally, being based on a FR schedule, this model focuses on drug-taking behavior, whereas compulsivity is as much a disorder of drug seeking as it is of drug taking.…”
Section: Instrumental and Pavlovian Mechanisms Subserving Drug Use: Dmentioning
confidence: 99%